Epithelial cell proliferation in the developing zebrafish intestine is regulated by the Wnt pathway and microbial signaling via Myd88 - Cheesman, Sarah E. (National Academy of Sciences, 2011)
Rates of cell proliferation in the vertebrate intestinal epithelium are modulated by intrinsic signaling pathways and extrinsic cues. Here, we report that epithelial cell proliferation in the developing zebrafish intestine is stimulated both by the presence of the resident microbiota and by activation of Wnt signaling. We find that the response to microbial proliferation-promoting signals requires Myd88 but not TNF receptor, implicating host innate immune pathways but not inflammation in the establishment of homeostasis in the developing intestinal epithelium. We show that loss of axin1, a component of the β-catenin destruction complex, results in greater than WT levels of intestinal epithelial cell proliferation. Compared with conventionally reared axin1 mutants, germ-free axin1 mutants exhibit decreased intestinal epithelial cell proliferation, whereas monoassociation with the resident intestinal bacterium Aeromonas veronii results in elevated epithelial cell proliferation. Disruption of β-catenin signaling by deletion of the β-catenin coactivator tcf4 partially decreases the proliferation-promoting capacity of A. veronii. We show that numbers of intestinal epithelial cells with cytoplasmic β-catenin are reduced in the absence of the microbiota in both WT and axin1 mutants and elevated in animals’ monoassociated A. veronii. Collectively, these data demonstrate that resident intestinal bacteria enhance the stability of β-catenin in intestinal epithelial cells and promote cell proliferation in the developing vertebrate intestine.